Challenges in reducing TIA clinic waiting times from 9 to 3 days in an acute Welsh hospital. Issue 4 (15th October 2018) - Krishnan, Manju; Jones, Andrew; Anjum, Tal; Chenna, Srikanth; Slade, Peter Michael Edward; Ward, Karen; Yeap, Sarah
Abstract : A patient impact project which successfully reduced the transient ischaemic attack (TIA) clinic waiting time from 9 to 3 days in an acute Welsh hospital, revealing the challenges faced and how alternative thinking and team work improved care given to our service users. Evaluating current situation, careful planning with multiple brainstorming meetings, 4 N chart and driver diagram with change ideas laid the foundation for this service improvement. Run charts, statistical process control and Pareto charts helped to identify the issues that are hindering the progress, which when rectified, reduced the clinic waiting times. Avoiding clinic cancellations by cross covering TIA clinics with mutual agreement among consultants and redeployment of ward staff to support clinics resulted in a positive impact to the patients. The average waiting time to see a patient in TIA clinic dropped from 9 days to just 3 days as a result of this, reflecting the hard-working and proactive nature of a team following a collaborative leadership journey. The service improvement initiative for 'avoiding clinic cancellations' was implemented in January 2017 and has reduced our waiting times by three times. Repeat analysis by six monthly Plan Do Study Act cycles revealed that this improvement is sustained.